Diversity of Seagrass Types and Conditions in the Waters of Suprau, Maladum Mes District - Goan Supit; Roger R. Tabalessy (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2024)
Seagrass beds are one of the ecosystems located in coastal areas or shallow marine waters. The uniqueness of seagrasses compared to other marine plants lies in their extensive root system and rhizome network. This type of rooting system causes seagrass leaves to become dense, which greatly benefits the productivity of the seagrass bed ecosystem. This study aimed to determine the species diversity and condition of seagrass beds on Suprau Beach, Maladum Mes District. Three seagrass species were found on Suprau Beach: Halodule pinifolia, Halodule uninervis, and Cymodocea serrulata, with relative cover percentages of 50%, 33.3%, and 16.7%, respectively. Based on the analysis of seagrass bed conditions in Suprau Waters, the ecosystem was classified as damaged or poor/unhealthy and impoverished according to the Indonesian Minister of Environment Decree No. 51 of 2004.